Crescimento econômico e pobreza em Moçambique: uma análise do crescimento pró-pobre (1996/97–2022/23) - Novela, Cristo Filipe (2025)
This dissertation investigates whether economic growth, income inequality, and poverty in Mozambique, based on panel data from the country‘s provinces, can be characterized as propoor. The study aims to assess whether economic growth is associated with poverty reduction and to identify the role of structural variables related to education, health, and sanitation. The econometric results indicate that economic growth has a negative and statistically significant effect on poverty, suggesting that increases in average income are associated with its reduction. Conversely, income inequality, measured by the Gini index, has a positive and significant effect, indicating that increases in inequality are associated with higher poverty, even when controlling for other socioeconomic factors. Among the structural variables, the gross enrollment rate was statistically significant and negatively associated with poverty, highlighting the importance of school progression and retention. Health infrastructure showed negative effects and, in some specifications, statistical or marginal significance, suggesting a relevant role in reducing socioeconomic vulnerability. In contrast, basic sanitation indicators were not statistically significant in the estimated models. Overall, the results indicate that poverty in Mozambique is consistently influenced by economic growth and income inequality, while broader educational progress and access to health services represent important structural channels explaining its dynamics.